“May we not orchestrate our own misfortune”: a qualitative study on perception about causes and prevention of occupational injuries among bricklayers and carpenters in Osun State, Nigeria - Temitope Olumuyiwa Ojo; Temitope Olumuyiwa Ojo; Nisha Naicker; Nisha Naicker; Funmilayo Juliana Afolabi; Adedeji Ayodeji Onayade (Frontiers in Public Health)
BackgroundOccupational injuries (OIs) remain a major public health concern in the construction industry, especially in developing countries where underreporting poses significant challenges. The belief systems of construction artisans may shape their perceptions of workplace hazards and safety practices, yet these dynamics remain underexplored in Nigeria. Hence, this study explored the beliefs about causes and prevention of OIs among artisans in the informal sector of the construction industry in Osun State, Nigeria.MethodsTwelve focus group discussions (FGDs) were conducted in Osun State, Nigeria, with six FGDs each held with bricklayers and carpenters. Each FGD comprised five to seven participants. A semi-structured FGD guide was employed to moderate the discussions. Each session was facilitated by a moderator and a note-taker. Verbatim transcription was done for FGD audios, the transcripts were coded and thematically analysed using the ATLAS.ti software. Relevant direct quotations illustrating the themes and subthemes were cited accordingly.ResultsSeventy artisans participated in the FGDs and all participants were male. The findings identified a range of beliefs about injury causation, with a strong emphasis on spiritual beliefs. These included notions of predestination by God and enchantment. However, a less common belief suggested that adherence to safety precautions could prevent injuries. Also, some participants expressed a nuanced combination of these perspectives. Perceptions of injury prevention were reflected in various subthemes, including the importance of prayers, avoiding conflicts, or taking jobs from others, maintaining safe housekeeping practices, government provision or subsidization of personal protective equipment (PPE) and its correct usage, provision of safety training and effective supervision.ConclusionWorkplace injuries among artisans were attributed to spiritual factors, limited access to safety equipment, and inadequate compliance with safety measures. Addressing these challenges requires culturally sensitive interventions, considering the perceptions of the artisans, alongside providing subsidized PPE, durable tools, targeted training, and effective supervision to foster a safer working environment and minimize injury risks.